Timorenses na Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB): encontros e desencontros de uma experiência - Nobre, Clarissa Diniz Diógenes (2015)
This essay analyses the integration process of students coming from East Timor to study at the University of International Integration of the Afro-Brazilian Lusophony (Unilab), from the perspective of the relationship between these students and the administrative and educational head of the university. It was verified that, besides the difficulties and challenges of any experience in a new country, this group had to deal with bureaucratic problems arising from the lack of consensus between the two parties regarding the implementation of the cooperation agreement between the university and the Timorese government. It is important to highlight this conflict to understand how the process of admission and residence of those students happens in the Institution; getting to understand also the continuity of relations between the Unilab and the Timor-Leste government. Through field research, it was possible to realize the strength of this group, that even in an environment where the African component is privileged, put into evidence the institutional thinking and the weaknesses of the university in relation to: a) meeting the demands of foreign students (in this case of the East Timor students); and b)the maintenance of international agreements. Throughout this work, besides the analysis of the integration process from the perspective of the relationship between East Timorese students and the administrative and educational head of the university; we observed how these students are involved in the academic life, that despite the differences, and the economic issue is just one of them, live together and interact spontaneously with other students of the institution.